REFLECTION OF GLOBAL LEARNING AND DEVELOPMENT TRENDS IN OFFICIAL NARRATIVES OF CANADIAN CORPORATIONS - Halyna Nosulich; Nataliya Mukan (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2020)
The paper dwells on how current L&D trends are followed by Canadian corporations and what their attitude to continuous learning is, considering that corporate narratives present in official documentation are relevant object for the research. In general, scientific inquiry of Canadian experience in the sphere of corporate education is relevant for comprehensive analysis as Canadian best practices can be applied by organisations of various types in other countries. The paper presents quantitative and qualitative data revealed in the process of content analysis of official narratives, their interpretation and correlations between the results and current L&D trends as outlined in the literature review. Thus, in the centre of the methodological framework of this research is content analysis. 21 general annual and sustainability reports of 13 Fortune 500 Canadian companies were sampled for extracted text narratives to be coded according to the predefined coding scheme and further interpreted. The research has allowed to answer the question whether official documentation issued by Canadian companies is resourceful for the study of corporate education in the country. The light was shed on types of reports which contain the most relevant information on the issue. The investigation revealed that the most frequent coded narratives are related to the continuous development of employees, alignment of L&D and business strategy, compliance training and inclusion & diversity training within organisations. The paper describes and discusses these results in detail as well as traces reflection of global L&D trends in corporate documentation.